A two‐dimensional organic–inorganic hybrid perovskite‐type semiconductor: poly[(2‐azaniumylethyl)trimethylphosphanium [tetra‐μ‐bromido‐plumbate(II)]]. Issue 3 (21st February 2019) - Cheng, Ling; Cao, Yingjie
Abstract : A twisted 2D layered anion structure is formed because of the infiltration of cations and the presence of hydrogen bonds. A band gap of ∼2.700 eV was found through experimental and theoretical studies. Abstract : Recently, with the prevalence of `perovskite fever', organic–inorganic hybrid perovskites (OHPs) have attracted intense attention due to their remarkable structural variability and highly tunable properties. In particular, the optical and electrical properties of organic–inorganic hybrid lead halides are typical of the OHP family. Besides, although three‐dimensional hybrid perovskites, such as [CH3 NH3 ]Pb X 3 ( X = Cl, Br or I), have been reported, the development of new organic–inorganic hybrid semiconductors is still an area in urgent need of exploration. Here, an organic–inorganic hybrid lead halide perovskite is reported, namely poly[(2‐azaniumylethyl)trimethylphosphanium [tetra‐μ‐bromido‐plumbate(II)]], (C5 H16 NP)[PbBr4 ] n, in which an organic cation is embedded in inorganic two‐dimensional (2D) mesh layers to produce a sandwich structure. This unique sandwich 2D hybrid perovskite material shows an indirect band gap of ∼2.700 eV. The properties of this compound as a semiconductor are demonstrated by a series of optical characterizations and indicate potential applications for optical devices.